THE ANALYSIS OF ADAPTIVE LEADERSHIP FACTORS FOR IMPROVING THE PERFORMANCE OF COMPANY ORGANIZATION - Sukmo Hadi Nugroho; Heru Kreshna Reza (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2020)
Adaptive Leadership will always be an important factor in determining the back and forth of a company. The leader must be able to provide direction for the vision of the future, then bring all employees to understand the vision, so that the company as a whole has the readiness to face any obstacles that stand in their way. This is what will then bring the company to the optimum point, where all the company's potential can be utilized for the progress of the company. Leaders with all the leadership factors inherent in themselves are related to the performance of their employees. This is very easy for anyone to understand. A leader who has a good leadership spirit will be able to create a good teamwork. The existence of good teamwork will greatly support the creation of a good and significant increase in employee performance. This study aims to determine the extent of employee performance and the role of leadership behavior on employee performance in organization companies. From the research results it is known that there is a significant relationship between the adaptive leadership factor and employee performance, with a correlation test result. The amount of influence exerted by the leadership factor on improving employee performance in organization companies. Keywords: Adaptive Leadership, Improving, Organization Performance.